The analgesic effectiveness of auriculotherapy for acute postoperative pain: A systematic review and meta-analysis - Guilin Zhang; Guixing Xu; Yao Tang; Lingxue Zhang; Xi Chen; Xingyu Liang; Ling Zhao; Dehua Li (Complementary Therapies in Medicine)
Background: Postoperative pain is a significant yet inadequately managed complication following surgery, and auriculotherapy to alleviate acute postoperative pain (APP) and reduce the use of opioids remains controversial. Methods: We searched the MEDLINE, Web of Science, Embase, Cochrane Library, CINAHL Complete, and ClinicalTrials.gov from inception to January 23, 2024 for all randomized controlled trials (RCTs) of auriculotherapy in the treatment of APP. The extracted data underwent risk of bias assessment, meta-analysis, subgroup analyses, sensitivity analysis, meta-regression analysis, and evidence rating. Results: A total of 24 studies involving 2131 patients were included in the meta-analysis. Low-quality evidence indicated that auriculotherapy was effective in reducing pain intensity at 24 [MD(95 %CI)=-0.64(-1.09, −0.19), I2=77 %, P＜0.01], 48 [MD(95 %CI)=-0.49(-0.97, 0.00), I2=71 %, P=0.05], and 72 [MD(95 %CI)=-0.80(-1.32, −0.28), I2=52 %, P＜0.01] hours after surgery, while moderate-quality evidence showed a decrease in total opioid consumption [MD(95 %CI)=-24.41 OME (-38.28, −10.54), I2=95 %, P＜0.01]. However, no significant effects were observed in reducing postoperative nausea or vomiting [RR(95 %CI)=0.61(0.32, 1.16), I2=71 %, P=0.13; RR(95 %CI)=0.32(0.09, 1.18), I2=71 %, P=0.09; RR (95 %CI)=0.34(0.11, 1.06), I2=28 %, P=0.06; for postoperative nausea and vomiting (PONV), postoperative nausea or postoperative vomiting respectively], with evidence ranging from moderate to very low. Additionally, two RCTs found that auriculotherapy could delay the time to the first request for analgesia. Conclusions: The summary estimates indicate that auriculotherapy may be beneficial in reducing APP and opioid consumption in specific surgeries based on low-to-moderate quality evidence. However, high-quality RCTs are still further studied in different surgical populations. Systematic Review Registration: PROSPERO database, CRD42024506989.